Characterisation of the host inflammatory response to Staphylococcus epidermidis in neonatal whole blood. Issue 2 (15th November 2007) - Härtel, C; Osthues, I; Rupp, J; Haase, B; Röder, K; Göpel, W; Herting, E; Schultz, C
Abstract : Background: Coagulase-negative staphylococci (CoNS) are the most prevalent pathogens causing late-onset sepsis, and gestational age is the most important risk factor for these infections. Objective: To characterise innate immune responses to S epidermidis by assessment of whole blood in vitro cytokine production in a large group of preterm and term infants. Results: The S epidermidis -induced in vitro production of proinflammatory cytokines such as intracytoplasmic interleukin (IL) 6 and tumour necrosis factor α in cord blood samples was found to be dependent on gestational age (R = 0.279, 95% CI 0.10 to 0.44, p = 0.002; R = 0.251, 95% CI 0.07 to 0.41, p = 0.005, respectively; n = 121). In contrast, the production of anti-inflammatory cytokines such as IL10 and transforming growth factor β was not associated with gestational age. When different stimulation strategies were compared, a strong correlation was noted for cytokine responses after lipopolysaccharide and S epidermidis exposure—that is, IL6 (R = 0.431, 95% CI 0.29 to 0.55, p<0.001, n = 161) and IL10 (R = 0.332, 95% CI 0.18 to 0.47, p<0.001, n = 161). In addition, a lower IL6 production was found in supernatants of whole blood cultures infected with a clinically isolated IcaABD -positive (biofilm production) strain compared with a control IcaABD -negative ATCC strain (p = 0.009). Conclusions: These in vitro data suggest that proinflammatory responses to S epidermidis are dependent on gestational age in preterm infants, whereas the counteracting anti-inflammatory response to S epidermidis may not be directly related to gestational age. Individual host factors may have a role as well as bacterial determinants, such as biofilm production. Further studies are encouraged to investigate the different aspects of innate immune responses to CoNS in vivo.